Removal of toxic aqueous ions using amorphous AlPO4. Issue 13 (1st September 2016) - Javid, Muhammad; Mustafa, Syed; Samreen, Tayyeba
ABSTRACT: Aluminium phosphate (AlPO4 ) was characterized using X-ray diffractometry (XRD), Fourier Transform infrared (FTIR), point of zero charge (PZC) and dissolution studies. XRD showed the sample to be amorphous, FTIR confirmed the presence of OH groups on the surface and PZC was determined at pH 3.45. The dissolution study illustrated a decrease in dissolution with an increase in the pH. Potentiometric titration data were fit to the Gaines–Thomas equation, which showed that AlPO4 is a weakly acidic ion exchanger. Sorption studies were carried out at pH 4–6 and temperatures 293–323 K. The uptake of metal ions was observed to increase with an increase in the pH and temperature. The surface selectivity towards metal ions was found in the order Pb 2+ > Cu 2+ > Cd 2+ . Sorption data were fit to the new equation derived from the proposed mechanism for metal ion uptake. Various parameters such as stoichiometry of the surface H + ion release, equilibrium constant, standard enthalpy, entropy and free energy changes were evaluated from the plots. The values of all these parameters were found to be closely related to the values reported in the literature.